2006
DOI: 10.1002/anie.200603450
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Rare‐Earth Polyhydrido Complexes: Synthesis, Structure, and Catalytic Activity for the cis‐1,4‐Selective Polymerization of 1,3‐Cyclohexadiene

Abstract: Metal hydrides are fundamental components in a wide range of stoichiometric and catalytic reactions. Their importance in modern inorganic and organic chemistry cannot be overemphasized. Rare-earth (Group 3 and lanthanide) hydrides are among the most active metal-hydride complexes. Together with their alkyl analogues, metal-hydride complexes of the rare-earth metals have occupied an especially important position in the development of the organometallic chemistry of the rare-earth elements. Generally, cationic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(49 citation statements)
references
References 56 publications
1
46
0
2
Order By: Relevance
“…In (Tardif et al, 2003), which represented the first examples of structurally well-defined, salt-free lanthanide polyhydrido clusters (Hou et al, 2001). These clusters and their derivatives could break strong bonds such as the C-O bond in CO (Shima and Hou, 2006) and CO2 (Tardif et al, 2004) and showed interesting polymerization activity (Li et al, 2006). A related trinuclear titanium polyhydride was found to be able to induce dinitrogen cleavage followed by partial hydrogenation in the presence of dihydrogen (Shima et al, 2013).…”
mentioning
confidence: 99%
“…In (Tardif et al, 2003), which represented the first examples of structurally well-defined, salt-free lanthanide polyhydrido clusters (Hou et al, 2001). These clusters and their derivatives could break strong bonds such as the C-O bond in CO (Shima and Hou, 2006) and CO2 (Tardif et al, 2004) and showed interesting polymerization activity (Li et al, 2006). A related trinuclear titanium polyhydride was found to be able to induce dinitrogen cleavage followed by partial hydrogenation in the presence of dihydrogen (Shima et al, 2013).…”
mentioning
confidence: 99%
“…The overall structure of the mono(THF)-containing polyhydride complexes 2-4 is almost the same as that of the THF-free Sc complex 1. In the case of the analogous complexes of larger metals such as Gd (5), [9] Dy (6), [9] and Ho (7), [9] an agostic interaction between the metal center and a methyl group of an adjacent C 5 is also observed, probably due to the greater steric unsaturation of these larger metal centers (Scheme 2). [9,10] These results show that the fine structures of the tetranuclear octahydride complexes are, to some extent, dependent on the ionic radius of the metal centers.…”
Section: Synthesis and Structures Of Tetranuclear Octahydrido Rare Eamentioning
confidence: 89%
“…Hydrogenolysis of the bis(trimethylsilylmethyl) complexes of larger rare earth metals such as Y, Er, and Tm in toluene affords the corresponding tetranuclear octahydride complexes [{(C 5 Me 4 SiMe 3 )Ln(µ-H) 2 } 4 (THF)] (2: Ln = Y; [8] 3: Ln = Er; [9] 4: Ln = Tm [9] ) where one of the four metal centers in these complexes bears an additional THF ligand (Scheme 2). The overall structure of the mono(THF)-containing polyhydride complexes 2-4 is almost the same as that of the THF-free Sc complex 1.…”
Section: Synthesis and Structures Of Tetranuclear Octahydrido Rare Eamentioning
confidence: 99%
“…The synthesis of well-defined polyolefin with reactive pendent vinyl group, which can be easily converted into functional groups by further chemical transformations, has drawn much attention over recent decades [1][2][3][4][5][6][7][8][9][10]. Among the various dienes successfully incorporated into the linear polyethylene (PE) or polypropylene (PP) main chain, the unsymmetrical dienes, such as p-(3-butenyl) styrene and dicyclopentadiene (DCPD), are very promising because of their two double bonds usually showing different selectivity toward coordinative incorporation and subsequent chemical transformation, respectively.…”
Section: Introductionmentioning
confidence: 99%